Health professionals and urban emblematization in the middle range city - Galarza, Bárbara (2016)
The aim of this study is to verify the hypothesis of incidence of the metropolitan scale as an epistemological obstacle in the study of health urban imaginaries in the middle range city. For this, we take into account the representations of health professionals and their local emblematic distinction in situations of migration, specialization and valorization as an ethnographic source. We then describe and analyze the social process through which professionals build up prestige locally. Actor’s migration paths are a key constituent element of this prestige which urban fabric is built upon native images of heroes and gods. This fabric, typical of the middle range urbanization, serves as a paradox that has the effect of converting health professionals from “laburantes” in the metropolis into “founding fathers” and “heroes” in the city of reference emblematized as “the city of work “. Research provides evidence showing how the social construction of professional prestige -linked to the production of local urban emblems- contributes to the production and reproduction of social segmentation that is promoted by the process of capitalist development in the middle range cities of the center of the province of Buenos Aires. In this process, the emblems of these cities, contrasting those of the metropolis, function as integrators that hinder the identity of the professional worker.